2012
DOI: 10.1186/1742-4682-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger arrays binding human papillomavirus types 16 and 18 genomic DNA: precursors of gene-therapeutics for in-situ reversal of associated cervical neoplasia

Abstract: BackgroundHuman papillomavirus (HPV) types 16 and 18 are the high-risk, sexually transmitted infectious causes of most cervical intraepithelial neoplasias (CIN) or cancers. While efficacious vaccines to reduce the sexual acquisition of these high-risk HPVs have recently been introduced, no virus-targeted therapies exist for those already exposed and infected. Considering the oncogenic role of the transforming (E6 and E7) genes of high-risk HPVs in the slow pathogenesis of cervical cancer, we hypothesize that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Since E6 gene had few GNN triplets it indicated that ZiFiT could not provide suitable hits. On similar lines, in a study by Wayengara, where zinc finger arrays were used to target HPV 16 and HPV 18 genome using ZiFiT software, only a set of unpaired zinc finger arrays of length 9 bp were obtained for E6 gene [ 32 ]. It is known that zinc fingers that recognize GNN triplets are well characterized and have been used to successfully design ZFNs to knockout several genes.…”
Section: Discussionmentioning
confidence: 99%
“…Since E6 gene had few GNN triplets it indicated that ZiFiT could not provide suitable hits. On similar lines, in a study by Wayengara, where zinc finger arrays were used to target HPV 16 and HPV 18 genome using ZiFiT software, only a set of unpaired zinc finger arrays of length 9 bp were obtained for E6 gene [ 32 ]. It is known that zinc fingers that recognize GNN triplets are well characterized and have been used to successfully design ZFNs to knockout several genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results in another study showed that using ZFNs to target HPV E7 induced specific shear of the E7 gene and attenuated its malignant biological effect. 150 Wayengera et al 151 computationally generated paired zinc-finger arrays (pZFAs) to target and cleave the genomic DNA of HPV-type 16 and 18, respectively. The authors highlighted the therapeutic effect of ZFN-mediated gene disruption in HPV 16/18, which was achieved when HPV-derived viral plasmids or vectors were introduced into precancerous lesions to realize targeted mutagenesis and gene-therapeutic reversal of cervical neoplasia.…”
Section: Viral Diseasesmentioning
confidence: 99%
“…The similar domains of E6 and E7 proteins allow the formation of telomeric complexes that possess interesting biological activities (78). The mutations in the zinc finger domain of E7 do not affect the ability to bind and deteriorate the pRB, but they do abrogate its ability to immortalize cells (79). In the human papillomavirus 83 (HPV83m) that produced cervical cancer, five mutations were found in the second zinc finger domain of E6, an important domain for protein-protein or protein-DNA interactions.…”
Section: Hpv E6/e7 Proteins and Zinc Fingersmentioning
confidence: 99%